PERSPEKTIF FAKTOR NORMA SUBYEKTIF DAN KONTROL KEPRILAKUAN TERHADAP PERILAKU KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Afiah, Efi Tajuroh; Dewi, Titi Navila; Kusumawati, Nugrahini (Gapenas Publisher, 2024)
Many factors affect taxpayer compliance, including; subjective norm factors and behavioral control. This study aims to determine the influence of subjective norm factors and behavioral control on the compliance of motor vehicle taxpayers. The research method used is quantitative research with a correlational approach method. The population is motor vehicle taxpayers. The technique of using samples uses simple random sampling to determine using the slovin formula. The results of the hypothesis test research show that subjective norms and behavioral control affect the compliance of motor vehicle taxpayers. Hypothesis 1 of the t-value calculated is 8.224 > the t-value of the table is 1.984 with a significance of 0.000 < 0.05 then (H1) is acceptable. Hypothesis 2 of a calculated t-value of 8.880 > a table t-value of 1.984 with a significance of 0.000 < 0.05 then (H2) is acceptable. Hypothesis 3 (Test F) value f calculated > f table (50.974 > 3.09) with significance (0.000 < 0.05), thus H3 was accepted. Based on the results of data analysis through proving the three hypotheses proposed in this study regarding the influence of subjective norms and behavioral control on the compliance of motor vehicle taxpayers, this study concludes that the three hypotheses proposed in this study are all accepted